Power Surge - Bova, Ben, 1932-2020 (Tor, 2015)
Dr. Jake Ross, the science advisor to a newly elected freshman senator, must figure out how Washington really works when his comprehensive energy plan runs afoul of special interests, cynical bureaucrats, and a powerful U.S. senator.